Integrating criminal careers and ecological research: the importance of geographic location for targeting interventions toward chronic and costly offenders - Allard, Troy (Crime & delinquency, 2017)
This study explored whether chronic and costly offenders were more likely to be from disadvantaged communities and whether the most disadvantaged communities accounted for higher proportions of chronic and costly offenders. The Semi-Parametric Group-Based Method was used and costs applied to the five offending trajectories. Moderate and chronic offenders represented 15.8% of the cohort but 70% of total costs. The Index of Relative Disadvantage was assigned based on the first recorded residential postcode and an ANOVA indicated that moderate and chronic offenders resided in communities that had more disadvantage. The 5% most disadvantaged communities were compared with other communities and were found to have higher concentrations of chronic and costly offenders. Implications for the efficient targeting of crime prevention programs and interventions are discussed.